A study on Chinese ancient jades with mercury alteration unearthed from Lizhou’ao Tomb - Bao, Yi (Sci Rep, 2019)
“Alteration” geologically refers to chemical composition and/or structural changes of minerals under the influences of hydrothermal fluids, surface water, seawater, or other environmental conditions. In this paper, we use the word “alteration” to refer to chemical component and structural changes in jade artifacts caused by human activity and natural weathering, which is different from the term in geology. “Mercury alteration”, a kind of black alteration related to Hg, is unique among the several types of alteration that occur in Chinese ancient jades. Mercury alteration often appears on ancient jade artifacts unearthed from high-grade tombs of the pre-Qin period (before 221 B.C.). Therefore, ancient jades with mercury alteration have attracted substantial attention from Chinese archaeologists. This paper reports the use of materials analytic techniques to study such ancient jade fragments. The studied jade samples date to the middle and late periods of the Spring and Autumn Period (~500 B.C.) and were unearthed from Lizhou’ao Tomb in Jiangxi Province, China. Structural analyses revealed the internal microstructure of the ancient jade fragments and the microdistribution of the mercury alteration. The jade fragments exhibit typical characteristics of round holes and structural hierarchy, which imply that the jades were heated before burial. The black alteration on these jade samples was found to be rich in Hg. The results of this study will be widely useful in the study of ancient jade artifacts and jade culture in Chinese archeology.